THE EFFECT OF CORPORATE SOCIAL RESPONSIBILITY, POLITICAL CONNECTION, AND OWNERSHIP STRUCTURE TO CORRUPTION RISK IN COMPANIES LISTED ON TRANSPARENCY INTERNATIONAL - Satila, Hanna Trusty; Chariri, Anis (Department of Accounting, Faculty of Economics & Business, Universitas Diponegoro, 2023)
This study aims to investigate the effect of corporate social responsibility, political connections and ownership structures on the corruption risk in a global scale. We utilize 116 largest multinational companies listed on the Transparency International Reports in the period of 2014 and 2016 sample. Data are then analyzed using Smart PLS 3 with the PLS Algorithm and Bootstrapping tests. The fundings show that corporate social responsibility influence the corruption risk whereas political connection and ownership structure positively affect the corruption risk. The study implies the importance of considering corporate social responsibility, political connection and ownership structure when assessing fraud risks of companies, especially corruption risks.